2002
DOI: 10.1103/revmodphys.74.703
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer dynamics studied using resonant core spectroscopies

Abstract: The authors review the use of core-level resonant photoemission and resonant Auger spectroscopy to study femtosecond charge-transfer dynamics. Starting from simple models of the relevant processes, they examine the rationale for this approach and illustrate the approximations and known subtleties for the inexperienced experimentalist. Detailed analysis of case studies of increasing complexity are taken up, as well as the connection to related approaches using both valence excitation and the core-level fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
436
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(454 citation statements)
references
References 183 publications
11
436
1
2
Order By: Relevance
“…Brühwiler et al have conducted in depth studies of the decay processes in matrix-isolated C 60 and thin films of C 60 compared to the bulk, 9,24 and found that there is evidence for localization of varying degrees for all absorption transitions possible below the ionization threshold. This can be ascertained by a strong manifestation of participator decay, measurable in both RESPES and indirectly via CIS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Brühwiler et al have conducted in depth studies of the decay processes in matrix-isolated C 60 and thin films of C 60 compared to the bulk, 9,24 and found that there is evidence for localization of varying degrees for all absorption transitions possible below the ionization threshold. This can be ascertained by a strong manifestation of participator decay, measurable in both RESPES and indirectly via CIS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…1d) leaves the system in a state similar to spectator decay plus an excitation of an electron from the LUMO out of the molecule. Auger electrons again have a constant kinetic energy and at the LUMO resonance will appear in the RPES at a binding energy that is shifted to even higher binding energy than the spectator feature by an amount corresponding to the cost of re-390 moving the electron from the LUMO (the energy difference between the normal Auger and spectator decay is referred to as the spectator shift, which for C 60 is on the order of 2 eV [21]). So while Auger and spectator electrons track with constant kinetic energy as a function of increasing photon energy, they cannot track back to the binding energy of the HOMO at the LUMO resonance because 395 no transition exists using only the electrons intrinsic to the molecule that can result in such a high kinetic energy electron emission.…”
Section: Discussionmentioning
confidence: 99%
“…The spectator channel, on the contrary, leads to an Auger-like final state with two holes, and the spectral lines exhibit a normal Auger behaviour. However, often the enhancement of the direct valence band PES is given by the combination of the two different photoemissionlike and Auger-like channels [12,15,[25][26][27] and, in order to distinguish between the two regimes, it is in principle necessary to perform measurements with a photon energy bandwidth smaller than the core linewidth.Exploiting the polarization properties of the light, the angle resolved and spin polarized detection of the decay products can allow in principle to perform highly differential experiments. Several works have been devoted to the study of dichroism in the resonant Auger decay (with focus on the spectator channels), in normal Auger emission and in RIXS [3,[28][29][30][31].…”
mentioning
confidence: 99%
“…The spectator channel, on the contrary, leads to an Auger-like final state with two holes, and the spectral lines exhibit a normal Auger behaviour. However, often the enhancement of the direct valence band PES is given by the combination of the two different photoemissionlike and Auger-like channels [12,15,[25][26][27] and, in order to distinguish between the two regimes, it is in principle necessary to perform measurements with a photon energy bandwidth smaller than the core linewidth.…”
mentioning
confidence: 99%
See 1 more Smart Citation